The MUSLIM FASHION CONSUMERS AND PURCHASING DECISION - Wulan Octaviani; Rosana Eri Puspita (Maro: Jurnal Ekonomi Syariah dan Bisnis, 2021)
This study aims to determine how much influence product quality, sales promotion, and Islamic branding have on purchasing decisions with purchase intention as an intervening variable in the Naisha brand. The focus of this research object is the customer of the Naisha brand who has transacted online. The research method used is quantitative, with primary data obtained through distributing questionnaires and interviews. The sampling technique used purposive sampling, and the number of respondents in this study was 96 respondents. The data analysis used includes instrument test, multiple linear regression analysis, statistical test, classical assumption test and path analysis. This study indicates that product quality, sales promotion, and Islamic branding partially and simultaneously positively and significantly affect buying interest in Naisha products. Other results indicate that the variable product quality, sales promotion, and Islamic branding positively and significantly affect purchasing decisions. The purchase intention variable has a mediating effect on other independent variables.